Dimensi Politik dalam Kisah Al-Qur’an - Yusuf Baihaqi (Studia Quranika, 2019)
There are many dimension in the content of the Qur’an. One of those dimention is the political dimension. The existence of verses that explicitly explain how the relationship of the leaders and their people, direct interaction of prophets and the roler of the era, strengthen relationship of Islam and politics that can’t be separated. This research focus on a discussion about the political dimension in the verses of Qur’an and the real form of political dimension from the the content of in the holy Qur’an. This research is based on the theory that the holy Qur’an was revealed as a direction for human one of the example is the fugure of prophet Muhammad as an ideal figure of leader who grouded egalitasion values among the people he led. While the figureof the Pharoh (Fir’aun) is real occurience of the dictatorship of a leader. As prophet Sulayman as exemplified his firm attitude of being a leader.